A nomogram including baseline prognostic factors to estimate the activity of second‐line therapy for advanced urothelial carcinoma. (May 2014) - Pond, Gregory R.; Agarwal, Neeraj; Bellmunt, Joaquim; Choueiri, Toni K.; Qu, Angela; Fougeray, Ronan; Vaughn, David; James, Nicholas D.; Salhi, Yacine; Albers, Peter; Niegisch, Günter; Galsky, Matthew D.; et al.
Abstract : Objective: To study the impact of the prognostic factors liver metastasis (LM), anaemia (haemoglobin [Hb] <10 g/dL), Eastern Cooperative Oncology Group performance status (ECOG‐PS) ≥1 and time from previous chemotherapy (TFPC) on the activity of second‐line therapy for advanced urothelial carcinoma (UC). Patients and Methods: Twelve phase II trials evaluating second‐line chemotherapy and/or biological characteristics ( n = 748) in patients with progressive disease were pooled. Progression‐free survival (PFS) was defined as tumour progression or death from any cause. The PFS rate at 6 months (PFS6) was defined from the date of registration and calculated using the Kaplan–Meier method. Response rate (RR) was defined using Response Evaluation Criteria in Solid Tumours (RECIST) 1.0. A nomogram predicting PFS6 was constructed using therms software package in R (http://www.r‐project.org ). Results: Data regarding progression, anaemia, LM, ECOG‐PS and TFPC were available from 570 patients in nine phase II trials. The overall median PFS was 2.7 months, PFS6 was 22.2% (95% confidence interval 18.8–25.9) and the RR was 17.5% (95% CI: 14.5–20.9%). For every unit increase in risk group, the hazard of progression in 6 months increased by 41% and the odds of response decreased by 48%. A nomogram was constructed to predict PFS6 on an individual patient level. The model was internally validated and was shown to have acceptable calibration performance. Conclusions: The RR and PFS6 vary as a function of baseline prognostic factors in patients receiving second‐line therapy for advanced UC. A nomogram incorporating prognostic factors facilitates the evaluation of outcomes across phase II trials enrolling heterogeneous populations and helps select suitable agents for phase III testing.